(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The objective of the study was to provide data on the prevalence of low birth weight (less than 2500 grams) and its possible risk factors in Bali, mainly prepregnancy weight of mother (BMI/body mass index), pregnancy nutrition status (cronic energy deficiency and anemia), pregnancy weight gain, pregnancy disease pattern, and demographic characteristics. The study design was retrospective study. Samples were mothers who had children under 12 months old in all public health centers (Puskesmas) in Province Bali. Data on birth weight and other variables was collected from 1575 samples recerded in healthy book for mother and child (Buku Kesehatan Ibu dan Anak/KIA). Univariate and multivariate analysis were performed. Multiple regression models, including variables on prepregnancy BMI, pregnancy nutrition status (cronic energy deficiency and anemia), pregnancy weight gain, pregnancy disease pattern, maternal age, education, parity, and mother’s occupation were constructed to examine relative effect their on the risk of low birth weight. Result: The prevalence of low birth weight infants was 5.7 % in the study sample. Significant risk factors for low birth weight from the univariate analysis were maternal age in pregnancy less than 20 years and more than 35 years (18.9% vs 8.1%, P0.05). Conclusion: Improving prepregnancy body mass index and weight gain during pregnancy are effective strategies which reduce and prevent low birth weight.